Penanganan Prokrastinasi Mahasiswa melalui Muhasabah Diri - Abd. Hamid Cholili; Aulia Zahwa Zainuddin; Tifa Sahara Rohma; Chindy Maulidya Alfayn; Nurkamala Dewi; Muhammad Mahbubi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
In higher education, students are not only required to study in class but students are also required to study independently. Students are not only required to learn academic material but also non-academic material. However, in meeting these demands, students can encounter several obstacles such as difficulty finding references or literature, managing study time well, interacting with friends and lecturers, or self-management. This results in students experiencing academic procrastination. Academic procrastination is a behavior in which you procrastinate a task or an activity in carrying out an assignment but it takes longer than the time allotted (Nisa D.S, 2023). Therefore, this research aims to determine the effectiveness of handling student academic procrastination through self-reflection. This research uses the Academic Procrastination scale instrument with 10 statement items and the Self-Muhasabah scale with 10 statement items. Data analysis uses the product-moment correlation method from Pearson. The purpose of this analysis is to find a correlation between self-reflection and academic procrastination in students. The findings of this research show that the results of the correlation between academic procrastination and self-Contemplation obtained a correlation coefficient of 0.854 and a significance value of p=<0.01, this shows that self-Contemplation influences dealing with students' academic procrastination.